Adapting to Retirement Community Life: Changes in Social Networks and Perceived Loneliness. (3rd June 2015) - Crisp, Dimity A.; Windsor, Tim D.; Butterworth, Peter; Anstey, Kaarin J.
Abstract : Improved social relationships and connectedness is a frequently cited benefit of retirement community living. However, few studies have prospectively investigated changes in loneliness or social networks following relocation. This study involved 83 Australians (aged 57–90 years) relocating to independent living units within a retirement community. A prospective longitudinal design was employed whereby data was collected prior to relocation, and 1, 6 and 12 months post relocation. Comparisons were made with a sample of community-dwelling ( N = 549) residents of the same age. Individual characteristics (e.g., personality characteristics) associated with change were also explored. Results indicated reduced loneliness and increased neighbour support networks following relocation. A reduction in contact with friends was also observed. This study provides an important contribution to our understanding of the initial impact of transitioning into a retirement community on personal relationships. Through exploring factors associated with successful transition, we can begin to understand the characteristics of those individuals most likely to thrive in this type of environment.